Students' Financial Literacy Through Educational Materials Based on Banjar Cultural Values - Raihanah Sari; Herry Porda Nugroho Putro; Rochgiyanti Rochgiyanti; Ersis Warmansyah Abbas; Mohd Mahzan Awang (Yayasan Keluarga Guru Mandiri, 2025)
Financial literacy is an essential skill that enables students to manage their finances effectively. However, a significant gap in financial literacy among junior high school students highlights the need for innovative teaching materials. This study aimed to enhance students' financial literacy through the Project-Based Learning (PBL) model. The research employed a Research and Development (RD) approach using the 4D development model by Thiagarajan. Two expert lecturers validated the teaching module, and two ninth-grade junior high school teachers evaluated its effectiveness. Data analysis utilized qualitative descriptive techniques and descriptive statistics to assess validation results and teacher responses. The findings revealed that the teaching materials achieved high validity, with an average Aiken's V score of 0.90 (Highly valid) for material aspects and 0.89 (Highly valid) for language aspects. Teacher feedback indicated a positive response, with an average score of 85.25% (Very Good). These results demonstrate the success of culturally contextualized teaching materials, specifically those based on Banjar community values, in improving students' financial literacy. This research contributes to educational science by integrating cultural elements into financial literacy education, offering a model for developing impactful and contextually relevant teaching resources.